2013
DOI: 10.1016/j.resp.2013.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory control in infants, children, and adults with bronchopulmonary dysplasia

Abstract: Bronchopulmonary dysplasia (BPD), or chronic lung disease of prematurity, occurs in ~30% of preterm infants (15,000 per year) and is associated with a clinical history of mechanical ventilation and/or high inspired oxygen at birth. Here, we describe changes in ventilatory control that exist in patients with BPD, including alterations in chemoreceptor function, respiratory muscle function, and suprapontine control. Because dysfunction in ventilatory control frequently revealed when O2 supply and CO2 elimination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 131 publications
1
15
0
Order By: Relevance
“…This finding may have important clinical implications. 5 We found that some preterm adults paradoxically hypoventilate with hypoxia.…”
Section: To the Editormentioning
confidence: 83%
“…This finding may have important clinical implications. 5 We found that some preterm adults paradoxically hypoventilate with hypoxia.…”
Section: To the Editormentioning
confidence: 83%
“…Specifically, normal responses of increased ventilation with hypoxia as well as decreased ventilation with hyperoxia may be altered. Persistent chemoreceptor dysfunction has been documented in survivors of BPD [ 156 , 157 ]. Inadequate response to hypoventilation and hypoxia may represent significant risk of morbidity in survivors of BPD who may also suffer co-morbid central airway disease or bronchomalacia.…”
Section: Long-term Outcomes Of Bpdmentioning
confidence: 99%
“…At this late preterm stage, neonatal lungs are in the early alveolar phase of development and thus a need for supplemental oxygen may reflect ventilation and perfusion abnormalities; these could be related to immature alveolar and vascular development, to chronic lung disease or to a combination of the two. The pathophysiology prompting treatment with supplemental oxygen at this point may be related not only to lung injury, but also to immature neurorespiratory control mechanisms, airway obstruction, airway hyperreactivity, or pulmonary hypertension 49 , 50 , 51 . Even as apnea becomes less frequent, intermittent hypoxia may continue 52 .…”
Section: Challenges In Characterization and Prediction Of Bpdmentioning
confidence: 99%